2002
DOI: 10.1097/00001756-200208070-00007
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation decreases superoxide dismutase activity in rat hippocampus and brainstem

Abstract: Sleep deprivation by the disk-over-water technique results in a predictable syndrome of physiological changes in rats. It has been proposed that reactive oxygen species (ROS) may be responsible for some of these effects. A variety of antioxidative enzymes such as superoxide dismutase (SOD) and glutathione peroxidase (GPx) help to regulate the level of ROS. In this study we investigated the effects of prolonged (5-11 days) sleep deprivation on the activities of SOD and GPx as well as the metabolic activity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
158
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(168 citation statements)
references
References 20 publications
8
158
2
Order By: Relevance
“…As changes in protein phosphorylation occur within minutes and are associated with alterations in cellular activities [Shaw et al, 1995;Asthagiri et al, 1999;King et al, 2006;Morii et al, 2006;Nunez Rodriguez et al, 2006], our results provide evidence that such alterations occur within the time frames associated with individual sleep-wake bouts in rats [Timo-Iaria et al, 1970;Tobler and Borbely, 1986]. In addition, these data are consistent with previous reports that examined regional phosphorylated protein expression by immunohistochemical methods [Cirelli and Tononi, 1998], levels of specific phosphoproteins [Guan et al, 2004;Basheer et al, 2005;Naidoo et al, 2005;Bandyopadhya et al, 2006;Davis et al, 2006], or enzymatic activities [Ramanathan et al, 2002;Mackiewicz et al, 2003;Naidoo et al, 2005] following SD. …”
supporting
confidence: 91%
See 1 more Smart Citation
“…As changes in protein phosphorylation occur within minutes and are associated with alterations in cellular activities [Shaw et al, 1995;Asthagiri et al, 1999;King et al, 2006;Morii et al, 2006;Nunez Rodriguez et al, 2006], our results provide evidence that such alterations occur within the time frames associated with individual sleep-wake bouts in rats [Timo-Iaria et al, 1970;Tobler and Borbely, 1986]. In addition, these data are consistent with previous reports that examined regional phosphorylated protein expression by immunohistochemical methods [Cirelli and Tononi, 1998], levels of specific phosphoproteins [Guan et al, 2004;Basheer et al, 2005;Naidoo et al, 2005;Bandyopadhya et al, 2006;Davis et al, 2006], or enzymatic activities [Ramanathan et al, 2002;Mackiewicz et al, 2003;Naidoo et al, 2005] following SD. …”
supporting
confidence: 91%
“…GSTs are a multi-gene family of proteins that are associated with the maintenance of cellular oxidationreduction [Pocernich et al, 2000;Zhu et al, 2006]. The failure to maintain the cellular oxidation state has been proposed to account for some of the deleterious effects of SD [D'Almeida et al, 1998;Ramanathan et al, 2002] and has long been associated with the detrimental effects of aging [Zhu et al, 2006]. It is interesting to note that an increase in gst pi 2 subunit mRNA was also reported following spontaneous sleep [Cirelli et al, 2004].…”
Section: Protein Expression Across Spontaneous Sleep-wakefulness Jourmentioning
confidence: 99%
“…This has been supported by animal studies where sleep loss caused oxidative damage in the brain (Ramanathan et al, 2002, Suer et al, 2011 and increased lipid peroxidation (Thamaraiselvi et al, 2012). However, some animal studies have found that one to two weeks of sleep deprivation had no effect on oxidative stress in any brain region, including protein oxidation and lipid peroxidation (D'Almeida et al, 1997, Gopalakrishnan et al, 2004).…”
Section: Sleep and Its Effect On Oxidative Stressmentioning
confidence: 82%
“…The activated PER and CRY in turn inhibit the activity of the CLOCK/ BMAL complex. In addition to this, recent biochemical and physiological studies have confirmed that sleep deprivation as a strong stressor for the body, increase the level of oxidative stress of the brain, resulting in cognitive dysfunction and memory loss [2].…”
Section: Introductionmentioning
confidence: 92%